NOTES ON THE TEREBRALIA PALUSTRIS (GRASTROPODA) FROM THE CORAL ISLANDS IN THE JAKARTA BAY AREA - Soemodihardjo, Subagjo; Kastoro, Widiarsih (Marine Research in Indonesia, 1977)
A dense population of Terebralia palustris occurs in many coral islands in the Jakarta Bay area, living usually in association with mangrove communities. A preliminary study on this gastropod has been carried out in two islands, Pulau Rambut and Pulau Burung, which concerned with population density and structure, length-weight relationship, rate of growth, and the effect of prolonged desiccation and starvation. Analyses were made on the properties of the substrate including soil component, organic matter content, pH, salinity, and daily temperature fluctuation at the soils surface.No less than 130 specimens per square meter were counted in the most densely populated place in Pulau Rambut. The length frequency distribution showed a bimodal histogram, and the length-weight relationship was represented by the following equation: W = 0.00024 L25534 where : W = dry weight in gram; L = length in milimeter.A number of young individuals were confined in a fenced area for growth study. During the first four-month they gained an average additional length of 10 mm. Out of water and starved this gastropod may survive for three months.